2021
DOI: 10.1590/0034-7167-2020-0984
|View full text |Cite
|
Sign up to set email alerts
|

Selenium concentrations in elderly people with Alzheimer’s disease: a cross-sectional study with control group

Abstract: Objective: To investigate possible differences in plasma and erythrocyte concentrations of selenium among elderly with and without a diagnosis of Alzheimer’s disease (AD). Methods: Cross-sectional study, performed with an elderly group with Alzheimer’s disease, diagnosed by a geriatric doctor, and compared to an elderly group without the disease, equaling gender, education, and age. Atomic absorption spectrophotometry determined plasma and erythrocyte concentrations of total selenium (Set). Results: The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…Among the studies that determined selenium concentrations in AD patients/controls, some reported lower plasma/serum/blood selenium in AD patients compared to controls [ 55 , 57 , 65 , 66 , 67 , 68 , 69 , 70 ], some did not find a difference [ 71 , 72 , 73 , 74 , 75 ], and one study found higher selenium in AD patients [ 76 ]. However, meta-analysis of serum/blood selenium in AD patients defined a decrease in the selenium level correlated with glutathione peroxidase in AD patients [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies that determined selenium concentrations in AD patients/controls, some reported lower plasma/serum/blood selenium in AD patients compared to controls [ 55 , 57 , 65 , 66 , 67 , 68 , 69 , 70 ], some did not find a difference [ 71 , 72 , 73 , 74 , 75 ], and one study found higher selenium in AD patients [ 76 ]. However, meta-analysis of serum/blood selenium in AD patients defined a decrease in the selenium level correlated with glutathione peroxidase in AD patients [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, selenium deficiency leads to increased Aβ plaque formation, tau protein hyperphosphorylation, and oxidative stress resulting in neurodegeneration (Haratake et al, 2013). In addition to this, AD patients, elders, and mild cognitive impairment patients have lesser amounts of selenium in their brains which is associated with memory and cognitive impairments (Nascimento et al, 2021; Pereira et al, 2022). Further, clinical and preclinical evidence suggests that selenium supplementation enhances cognitive and memory function in elders, AD patients, and experimental animals indicating that the dietary intake of selenium is essential to improve memory and brain health (Pereira et al, 2022; Tamtaji et al, 2019).…”
Section: Cruciferous Phytochemicals and Their Neuroprotective Activitiesmentioning
confidence: 99%
“…It is a vital component of many enzymes (i.e., selenoproteins) that help synthesize and protect DNA, and regulate thyroid function and reproduction [248]. Clinical studies have investigated the link between circulating levels of selenium and cognitive function, amyloid status, or AD risk [229][230][231][232][233][234]. Serum concentrations of selenium and its related total antioxidant status (TAS) [235] or the selenium content in erythrocytes among the AD patients [233] were significantly lower compared to those in healthy elderly group.…”
Section: Seleniummentioning
confidence: 99%
“…Clinical studies have investigated the link between circulating levels of selenium and cognitive function, amyloid status, or AD risk [229][230][231][232][233][234]. Serum concentrations of selenium and its related total antioxidant status (TAS) [235] or the selenium content in erythrocytes among the AD patients [233] were significantly lower compared to those in healthy elderly group. Similarly, a cross-sectional study on 469 elderly individuals from rural counties in China reported that higher serum levels of selenium are strongly associated with lower serum Aβ42 and Aβ40 [198], indicating a possible neuroprotective role of selenium.…”
Section: Seleniummentioning
confidence: 99%